Avaliação do efeito probiótico de Akkermansia muciniphila BAA-835 em modelo murino de alergia alimentar - Vívian Correia Miranda (2023)
Food allergy is triggered when there is an abnormal activation of the immune system by food allergens. One of the strategies that have been studied for the treatment of food allergy is the use of probiotics, considering their immunomodulatory effects. Therefore, the aim of this study is to evaluate the probiotic effect of Akkermansia muciniphila BAA-835 in an in vivo model of food allergy, analyzing clinical, immunological, histological and microbiological parameters. In addition, the effect of the viability and the association with Bifidobacterium longum 51A were also evaluated. For this purpose, mice were sensitized with ovalbumin (OVA) (day 0). After 14 days they received a booster. The control group received only the adjuvant with saline by day 0 and only saline on 14th day. On 18th day, mice received daily the respective treatment of 1x109 UFC of A. muciniphila viable or inactivated or associated with B. longum 51A until the end of the experiment (day 28). The control group received only saline. From 21st day mice were challenged with a diet containing OVA. On 28th day mice were euthanized. Oral administration of viable A. muciniphila led to a significant attenuation of the body weight loss, tissue damage, levels of IgE and IgG1 anti-OVA, eosinophils, neutrophils, eotaxin-1, CXCL1/KC and levels of pro-inflammatory cytokines (IL4, IL6, IL9, IL13, IL17 and TNF). However, it did not change the levels of IL10 (anti-inflammatory cytokine). Allergic mice showed a significant increase in Staphylococcus levels and total yeast frequency. In contrast, the treated group showed a reduction in Staphylococcus levels and in the frequency of total yeast. However, the bacteria did not promote a significant attenuation in the levels of intestinal permeability. In addition, the oral administration of the bacterium inactivated by heat (75ºC) was able to significantly reduce the IgE anti-OVA and eosinophil levels. Lastly, the association of A. muciniphila with B. longum 51A did not improve the effects presented by A. muciniphila in food allergy, aggravating the signs of inflammation. Our data demonstrate that the oral administration of viable and heat-inactivated A. muciniphila BAA-835 promotes a systemic immunomodulatory effect in the analyzed model, which suggests its probiotic and postbiotic properties.